2013
DOI: 10.1089/tmj.2012.0201
|View full text |Cite
|
Sign up to set email alerts
|

Home Telehealth: Facilitators, Barriers, and Impact of Nurse Support Among High-Risk Dialysis Patients

Abstract: The results suggest that home telehealth self-monitoring with RCN support is effective in empowering patients to take a more active role in their healthcare and indirectly improve quality of life for those living with chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…In the literatures, patients used SM solutions to manage their conditions by engaging in activities such as setting goals, monitoring their condition and adjusting medication. From the patient perspective, factors influencing adoption of these solutions included knowledge of their condition [ 10 , 11 , 31 , 35 , 36 , 38 , 45 , 50 , 58 , 62 , 72 , 82 ], their capability to comprehend and operate the solutions, their ability to embed or customise solutions into daily practices [ 33 , 39 , 41 , 44 , 46 , 56 , 57 , 69 ], visible effect of the solution [ 10 , 43 , 66 , 67 , 74 ], cost and quality of the solutions and their effectiveness to manage the condition such as sending accurate readings [ 33 , 35 , 45 , 52 , 61 , 70 , 71 , 79 ], family and healthcare professional support [ 9 , 39 , 40 , 50 53 , 58 , 75 ], the need for motivational factors [ 35 , 41 , 45 ] and their ability to make decisions on adjusting medication independently [ 61 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literatures, patients used SM solutions to manage their conditions by engaging in activities such as setting goals, monitoring their condition and adjusting medication. From the patient perspective, factors influencing adoption of these solutions included knowledge of their condition [ 10 , 11 , 31 , 35 , 36 , 38 , 45 , 50 , 58 , 62 , 72 , 82 ], their capability to comprehend and operate the solutions, their ability to embed or customise solutions into daily practices [ 33 , 39 , 41 , 44 , 46 , 56 , 57 , 69 ], visible effect of the solution [ 10 , 43 , 66 , 67 , 74 ], cost and quality of the solutions and their effectiveness to manage the condition such as sending accurate readings [ 33 , 35 , 45 , 52 , 61 , 70 , 71 , 79 ], family and healthcare professional support [ 9 , 39 , 40 , 50 53 , 58 , 75 ], the need for motivational factors [ 35 , 41 , 45 ] and their ability to make decisions on adjusting medication independently [ 61 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar sentiments were evident in ‘shared-decision making’ in that whilst some individuals preferred to take active part in the decision-making on their conditions [ 37 , 77 ], others were not confident or would rather leave decision-making to healthcare professionals, which decreased adoption [ 59 , 79 ]. Hence, empowerment was a facilitator for some [ 10 , 37 , 39 , 72 , 77 ], but not for others [ 59 , 72 , 79 ]. In diabetes self-management for example, Murphy and colleagues found that ‘being in control’ was the overall outcome that could be expected when a person was empowered to implement the Dose Adjustment For Normal Eating (DAFNE) principles to self-manage their diabetes; however, some participants found that DAFNE took more time, and found the uncertainty unsettling and the self-responsibility difficult, and quoted a participant saying: But I just have not got the determination nor the lifestyle, nor do I suppose really, do I want to be tied to it… [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent RCT, Tang et al [ 36 ] found that nurse-led, multi-disciplinary telehealth interventions were effective in improving A1C outcomes. In another nurse-led telehealth intervention designed for high-risk dialysis patients, the participants reported being more empowered and better able to provide needed self-management of illness [ 37 ]. In a recent RCT, Young et al found that a telehealth nurse coaching model for people with diabetes produced higher self-efficacy scores in the control group than for those who received the usual care [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 5 ] This is particularly important when patients are managing self-care processes such as home dialysis. [ 6 , 7 ] By RM and trend analysis of physiological parameters, the technology enables early detection of deterioration of non-compliance and a patient’s clinical condition. There is increasing evidence that RM data can help physicians and nurses to proactively manage a patient’s treatment.…”
Section: Introductionmentioning
confidence: 99%